Space-Time Perspectives on Early Colonial Moquegua - Rice, Prudence M. (Book collections on Project MUSE., 2013)
In this rich study of the construction and reconstruction of a colonized landscape, Prudence M. Rice takes an implicit political ecology approach in exploring encounters of colonization in Moquegua, a small valley of southern Peru. Building on theories of spatiality, spatialization, and place, she examines how politically mediated human interaction transformed the physical landscape, the people who inhabited it, and the resources and goods produced in this poorly known area. Space-Time Perspectives on Early Colonial Moquegua looks at the encounters between existing populations and newcomers.